Pengaruh motivasi dan disiplin kerja terhadap kinerja karyawan PT. Babussalam Baru bagian pemasaran - Ronal, Rian; Hendriani, Susi; Ibrahim, Restu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of motivation and discipline of employees working on the performance of PT. Babussalam Baru Marketing Department. As for the population in this study is part of a marketing employee who numbered 68 people and made entirely in the study sample using census method. Analysis of the data used is descriptive analysis, but it is also a quantitative analysis that is using multiple linear regression with SPSS version 22. From the results of the testing that has been done, simultaneous regression test ( F-test ) showed that motivation and discipline and simultaneously significant effect on employee performance. Partial test results ( t test ) showed that motivation and discipline variables significantly influence the performance of the employees of PT. Babussalam Baru. Based on the results of the analysis carried out then the company should further improve the way employees work for the performance of employees can be improved further. The company also had to increase employee motivation by improving the policy so that it can be accepted by the employee, in addition to the discipline employees must also be increased again in order, so that the employee earnest and serious in completing the work.Keywords : Motivation, Discipline and Performance